2015
DOI: 10.1017/fms.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Equivalence Relations Satisfying Hyperarithmetic-Is-Recursive

Abstract: We prove, in ZF + Σ 1 2 -determinacy, that, for any analytic equivalence relation E, the following three statements are equivalent: (1) E does not have perfectly many classes, (2) E satisfies hyperarithmetic-is-recursive on a cone, and (3) relative to some oracle, for every equivalence class[Y ] E we have that a real X computes a member of the equivalence class if and only if ω1 . We also show that the implication from (1) to (2) is equivalent to the existence of sharps over Z F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Definitions analogous to this were given by Liang and Montalbán . Under this notion the classical degree spectrum of a structure scriptA is prefixDgSpfalse(scriptAfalse).…”
Section: Introductionmentioning
confidence: 98%
“…Definitions analogous to this were given by Liang and Montalbán . Under this notion the classical degree spectrum of a structure scriptA is prefixDgSpfalse(scriptAfalse).…”
Section: Introductionmentioning
confidence: 98%
“…Remark (a) Montalbán proved that under the axiom of ‐determinacy an analytic equivalence relation E on 2 ω does not have perfectly many classes exactly when there is some εN such that for all αnormalTε every xnormalhα is E ‐equivalent to some ynormalTα (the latter property is called HYP‐is‐recursive on a cone ). Moreover he showed that the converse direction is in fact provable in sans-serifZF.…”
Section: The Characterizationmentioning
confidence: 99%
“…The proof of the converse direction when we have an arbitrary 1 1 equivalence relation E in a recursive Polish space X is exactly the same. [11] proved that under the axiom of 1 1 -determinacy an analytic equivalence relation E on 2 ω does not have perfectly many classes exactly when there is some ε ∈ N such that for all α ≥ T ε every x ≤ h α is E-equivalent to some y ≤ T α (the latter property is called HYP-is-recursive on a cone). Moreover he showed that the converse direction is in fact provable in ZF.…”
Section: Proposition 22 For Every Recursive Polishmentioning
confidence: 99%
See 2 more Smart Citations